A Perspective on Corrections Health Care - Jeffrey Beard (Washington University Journal of Law & Policy, 2006)
I believe that objective criteria are needed to measure the safety of our systems and facilities. In addition, a critical component of any evaluation needs to be actual visits to the facilities that are being evaluated. If this does not occur, and if we rely on anecdotal statements and reports as well as questionable statistical information, I am concerned that we may miss an opportunity to really make a difference by failing to focus on issues that can improve our system.
Keywords: Prison administration; Health services accessibility; Correctional institutions; Health services administration; Prisoners; United States